Colloid cyst of the third ventricle, hypothalamus, and heart: a dangerous link for sudden death - Turillazzi Emanuela; Bello Stefania; Neri Margherita; Riezzo Irene; Fineschi Vittorio (BMC, 2012)
Abstract Colloid cysts are rare congenital, intracranial neoplasms, commonly located in the third ventricle. Colloid cysts are endodermal congenital malformations. The cysts commonly range in size from 1-2 cm in diameter, although large cysts >3 cm in size have been reported. The components of the cyst include an outer fibrous capsule over an inner epithelium. The epithelium is usually a single layer of mucin-producing or ciliated cells. Such cysts contain mucoid and gelatinous material, which is positive for both Periodic acid Schiff (PAS) and mucicarmen staining. Although colloid cysts usually represent histopathologically benign neoplasms, they can result in sudden, unexpected and potentially lethal complications. The mechanism(s) of death is still a controversial subject and several mechanisms have been postulated to explain the sudden onset of severe symptoms and of fatal rapid deterioration in patients with colloid cysts. In this case, macroscopic and histological findings addressed the diagnosis of colloid cyst of the third ventricle with diffuse myocardial injury (coagulative myocytolysis or contraction band necrosis, CBN) and led us to conclude that acute cardiac arrest due to hypothalamus stimulation in the context of colloid cyst of the third ventricle was the cause of death. As the hypothalamic structures which are involved in neuroendocrine and autonomic regulation playing a key role in cardiovascular control are located close to the walls of the third ventricle which is the most frequent anatomical site of colloid cyst, this may suggest that reflex cardiac effects due to the compression of the hypothalamic cardiovascular regulatory centers by the cyst explain the sudden death in patients harboring a colloid cyst when signs of hydrocephalus or brain herniation are lacking. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/4915842848034158